DIPG-08. THE ROLE OF KMT5B/C AND H4K20 DI/TRIMETHYLATION IN DIPG. (23rd April 2019) - Kessler, Ketty; Mackay, Alan; Molinari, Valeria; Burford, Anna; Bjerke, Lynn; Temelso, Sara; Vinci, Mara; Jones, Chris
Abstract: Diffuse intrinsic pontine glioma (DIPG) are incurable childhood brain tumours marked by alterations in histone 3 in the form of somatic K27M mutations and loss of H3K27 trimethylation (H3K27me3). These highly aggressive tumours display extensive intratumoral heterogeneity, despite their relatively modest mutational burden. We recently proposed a model whereby co-operative subclonal interactions may exist to promote tumorigenesis in DIPG, and identified rare cancer stem cell populations to harbour mutations in the histone H4 lysine methyltransferase KMT5B . Although not previously described in glioma, loss of H4K20me2/3 caused by abrogated H4 methyltransferase function has been linked to defects in the DNA damage response and enhanced invasion in breast and pancreatic cancer. In order to explore whether dysregulation of H4 methylation may be directly responsible for tumorigenic phenotypes in DIPG, we targeted the methyltransferases by genetically engineering numerous isogenic cells from patient-derived in vitro models using CRISPR/Cas9 to knock out KMT5B and/or KMT5C, alongside pharmacological treatment with the small molecule KMT5B/C inhibitor A-196. We observed the expected reduction in H4K20me2 and H4K20me3 in response to inhibition of KMT5B/C, with an attendant increase in H3K27me3. Knock-out of KMT5B caused a significant increase in tumour cell migration and invasion in vitro, whilst KMT5C -deficient cells had reduced motility. Double knock-outs presented an intermediate phenotype. With H4K20me2/3 playing an important role in DNA repair via 53BP1 recruitment, we further observed a significantly enhanced efficacy of the PARP inhibitors olaparib and talazoparib in knock-out DIPG cells in vitro . Ongoing analysis of differential binding of post-translational modifications by ChIP-seq will provide important insights into the underlying mechanisms of epigenetic dysregulation, particularly in respect of the cross-talk between H3 and H4 marks. Although often present only in small tumour cell populations, H4K20me2/3 and KMT5B/C may represent an important novel aspect of DIPG tumorigenesis.